GIVING FEEDBACK TO LEARNERS AND TYPES OF FEEDBACK - Qo’chqorova Zulfizar Abduxamidovna; Obidova Shoxistaxon Nuridinjon qizi (Лучшие интеллектуальные исследования, 2024)
Abstract: This article focuses on how to give feedback to learners correctly and types of feedback. The paper aims to provide valuable constructions about giving feedback to students and various types of feedback. Since giving effective feedback is still an issue for many educators this paper aims to help educators, students and educational institutions make the best decisions when it comes to giving feedback and choosing its type by exploring different studies, scholarly articles, and real-life examples.